2023
DOI: 10.26668/businessreview/2023.v8i8.2995
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Management Strategies for Urban Hotels in China Under the Sustainable Development Goals of Low-Carbon Tourism

Abstract: Purpose: The objective of this study is to seek out common problems and improvement strategies in the management of urban hotels in China under the Sustainable Development Goals of low-carbon tourism. As significant contributors to carbon emissions in the tourism industry, urban hotels in China face various challenges in their operations. It is worth exploring the specific problems they encounter and how to enhance the management of urban hotels, along with strategies for improvement.   Theoretical framework: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…The achievement of energy saving in green marketing can be greatly refined depends on the effort that the industry make (X. . Additionally, there are circular economy theory and low-carbon economy theory that can explain about how energy efficiency and recycling are important circulation of economy in green marketing (Shanshan et al, 2023). Internationally, energy efficiency of tourism and hospitality research has been extremely active and reached a high level However, countries like Ghana lack the sustainable energy system (Appiah et al, 2023).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…The achievement of energy saving in green marketing can be greatly refined depends on the effort that the industry make (X. . Additionally, there are circular economy theory and low-carbon economy theory that can explain about how energy efficiency and recycling are important circulation of economy in green marketing (Shanshan et al, 2023). Internationally, energy efficiency of tourism and hospitality research has been extremely active and reached a high level However, countries like Ghana lack the sustainable energy system (Appiah et al, 2023).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…SCM is a new management method based on the rational integration of internal and external resources, and it is the management of the overall coordination of the enterprise's supplier network, the core enterprise and the enterprise's sales network. Shanshan et al(2023) showed that the value of the hotel was increased, so they have high requirements for hotel service level, product quality, supply speed, and service attitude. According to Dzalbs and Kalganova (2020), it is necessary to establish inventory to ensure the delivery rate of products, and it is necessary to establish an inventory control strategy to ensure the delivery rate.…”
Section: Research On Improvement Of Hotel Supply Chain Resource Manag...mentioning
confidence: 99%
“…These global regulations aim to address pollution, depletion of natural resources, and other environmental concerns. A new area of law concerning the environment and humanity has emerged: international law against the backdrop of sustainable development [6].…”
Section: Introductionmentioning
confidence: 99%